Physical Properties, Chemical Structure, and Microstructure of Thermoplastic Polyurethane Recycled Material-Modified Asphalt - Peng Yang; Peiliang Cong; Hongjie Hao; Pengfei Xiong (Buildings)
Firstly, thermoplastic polyurethane recycled material (TPRM) particles were used to prepare modified asphalt. Then, the modified asphalt’s physical properties were investigated. The results show that the TPRM particles improved its high-temperature performance, low-temperature crack resistance, and shear behavior due to its increased cohesion and low-temperature fracture energy levels. Thermal susceptibility was affected by the degree of swelling and dissolution of the TPRM particles, the composition of the asphalt, and the interface effect between the asphalt molecules and both the regular and slender–irregular TPRM particles. The TPRM particles swelled and dissolved after absorbing the light components of asphalt. Changes in the shearing temperature and time made the TPRM particles swell and dissolve more than changes in the activation temperature and time. An increase in the shearing/activation temperature and time increased the hydrogen bond content in the modified asphalt due to the rearrangement of the polyurethane’s molecular structure and the hydrogen bonds formed by the asphaltene and polyurethane molecules. Slender–irregular TPRM and “sea–island” and hilly and gulley structures were found in the modified asphalt matrix.